Analysis of the SPT-140 Thruster Mechanical Strength. (2017) - Olshanskaya, O.V.; Usanov, A.U.
Abstract: Stationary plasma thrusters, including the new generation SPT-140 thruster, are finding a wider application aboard spacecraft with increased requirements in terms of resistance to external mechanical loads. When designing a thruster, one of the most important requirements is to ensure its mechanical resistance to external factors. Based on the comparative analysis of thruster application conditions for different programmes and based on the strength analysis results with the use of the finite-element model, and on the mechanical test results of the thruster experimental models, a possibility of using the thruster with some modifications on modern spacecraft with increased requirements in terms of resistance to external mechanical loads is demonstrated.